2002
DOI: 10.1093/sw/47.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Implementing TANF in New York: The Perspective of Frontline Workers

Abstract: The study discussed in this article examined the perspectives of front-line welfare workers on issues related to the implementation of TANF: domestic violence, work requirements, time limits for cash benefits, and functions of workers. Based on focus groups held in upstate New York, findings suggest a lack of criteria for the granting of exemptions from TANF requirements, worker resistance to serving those caught in the cycle of violence, and congruence between the legislation's "work first" strategy and worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 10 publications
2
52
0
Order By: Relevance
“…Some workers further expressed a belief that women experiencing domestic violence need to take action to end the abuse before the worker will provide assistance. This finding is consistent with previous research, which suggests that frontline workers impose additional criteria on battered women rather than utilizing the services offered under the FVO to maximize women's safety resources (Hagen and Owens-Manley 2002). Coupled with mounting evidence of the danger facing women who leave batterers (Campbell et al 2003), this stance could contribute to increasing women's risk instead of alleviating it.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some workers further expressed a belief that women experiencing domestic violence need to take action to end the abuse before the worker will provide assistance. This finding is consistent with previous research, which suggests that frontline workers impose additional criteria on battered women rather than utilizing the services offered under the FVO to maximize women's safety resources (Hagen and Owens-Manley 2002). Coupled with mounting evidence of the danger facing women who leave batterers (Campbell et al 2003), this stance could contribute to increasing women's risk instead of alleviating it.…”
Section: Discussionsupporting
confidence: 87%
“…However, they are found to be less likely to supply exemptions in client situations in which battered women returned to the abuser (as is frequently the case for women coping with domestic violence). Congruent with MaynardMoody and Musheno's thesis (2003), Hagen and Owens-Manley (2002) indicate that frontline workers use their discretionary powers to reward clients they believe are deserving (i.e., compliant and working toward agency goals).…”
Section: Preliminary Evaluations Of the Fvomentioning
confidence: 97%
“…Lindhorst and Padgett (2005) identify organizational factors such as the focus on case closure, lack of time to carry out thorough interviews because of high client-to-staff ratios, and inadequate training in responding to abuse as impediments to screening for domestic violence. Workers have also been found to harbor negative judgments of clients that are communicated directly and indirectly, which act as obstacles to disclosing abuse (Hagen & Owens-Manley, 2002;Lindhorst & Padgett, 2005;Saunders et al, 2005). Similar structural dynamics may be occurring in the settings under investigation here, and may be pervasive in the current welfare system.…”
Section: Discussionmentioning
confidence: 64%
“…In a study conducted after welfare reform, Hagen and Owens-Manley (2002) found that frontline workers generally expressed agreement with the new emphasis in the TANF program on employment and acknowledged a clear philosophical shift from granting money to requiring work; however, they questioned TANF's effectiveness for long-term welfare recipients and those needing additional assistance to achieve economic self-sufficiency. Gais et al (2001), on the other hand, found that frontline staff almost always mentioned the required work activities during the initial application process with participants, reflecting the new emphasis on "WorkFirst."…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hagen and Owens-Manley (2002), in a study of decision making among frontline staff regarding the domestic violence exemption, found that most staff placed primary emphasis on the participant's efforts to help herself and gave lower priority to participants who repeatedly returned to a violent partner and were more dependent on welfare. Hasenfeld et al's (2004) and Keiser et al's (2004) findings that participants of color were more likely to be sanctioned by frontline staff when compared to White participants suggests two possibilities.…”
Section: Introductionmentioning
confidence: 99%